# arrow_back Find the derivative of $f(x)=3 / x^{4}-2 x^{2}+6 x-7$.

73 views
Find the derivative of $f(x)=3 / x^{4}-2 x^{2}+6 x-7$.

$f^{\prime}(x)$

$=\frac{d}{d x}\left(\frac{3}{x^{4}}-2 x^{2}+6 x-7\right)$

$=\frac{d}{d x}\left(3 x^{-4}-2 x^{2}+6 x-7\right)$

$=-12 x^{-5}-4 x+6$
by Platinum
(119,120 points)

## Related questions

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Find the derivative $f(x)=(3 x-2) \times (5 x+6)$
Find the derivative $f(x)=(3 x-2) \times (5 x+6)$Find the derivative $f(x)=(3 x-2) \times (5 x+6)$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Find the derivative $f(x)=\frac{(3 x-2)}{(5 x+6)}$
Find the derivative $f(x)=\frac{(3 x-2)}{(5 x+6)}$Find the derivative $f(x)=\frac{(3 x-2)}{(5 x+6)}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Find the derivative of $f(x)=3 x^{2}+2 x-1$
Find the derivative of $f(x)=3 x^{2}+2 x-1$Find the derivative of $f(x)=3 x^{2}+2 x-1$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
If $g(x)=2 x^{3}+\ln x$ is the derivative of $f(x)$, find $$\lim _{x \rightarrow 0} \frac{f(1+x)-f(1)}{x}$$
If $g(x)=2 x^{3}+\ln x$ is the derivative of $f(x)$, find $$\lim _{x \rightarrow 0} \frac{f(1+x)-f(1)}{x}$$If $g(x)=2 x^{3}+\ln x$ is the derivative of $f(x)$, find $$\lim _{x \rightarrow 0} \frac{f(1+x)-f(1)}{x}$$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Find the derivative of $f(x)=x^{3}$.
Find the derivative of $f(x)=x^{3}$.Find the derivative of $f(x)=x^{3}$. ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Find the derivative of $f(x)=x^{5}+5 x^{2}$.
Find the derivative of $f(x)=x^{5}+5 x^{2}$.Find the derivative of $f(x)=x^{5}+5 x^{2}$. ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Given that $f(x)=5 x^{2}-4 x+3$, find the coordinates of the point where the gradient is 6
Given that $f(x)=5 x^{2}-4 x+3$, find the coordinates of the point where the gradient is 6Given that $f(x)=5 x^{2}-4 x+3$, find the coordinates of the point where the gradient is 6 A. $(4,1)$ B. $(4,-2)$ C. $(1,4)$ D. $(1,-2)$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Given that $\frac{6 x+m}{2 x^{2}+7 x-15} \equiv \frac{4}{x+5}-\frac{2}{2 x-3}$, find the value of $m$.
Given that $\frac{6 x+m}{2 x^{2}+7 x-15} \equiv \frac{4}{x+5}-\frac{2}{2 x-3}$, find the value of $m$.Given that $\dfrac{6 x+m}{2 x^{2}+7 x-15} \equiv \dfrac{4}{x+5}-\dfrac{2}{2 x-3}$, find the value of $m$. A. 20 B. 12 C. $-10$ D. $-22$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Find the limit $\lim _{x \rightarrow \infty} \frac{6 x^{2}-4 x^{5}+7 x-1}{12 x^{5}-3 x^{2}+2}$
Find the limit $\lim _{x \rightarrow \infty} \frac{6 x^{2}-4 x^{5}+7 x-1}{12 x^{5}-3 x^{2}+2}$Find the limit $\lim _{x \rightarrow \infty} \dfrac{6 x^{2}-4 x^{5}+7 x-1}{12 x^{5}-3 x^{2}+2}$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
If $f(x)=\frac{4-5 x}{2}$, and $g(x)=x+6, x \in R$, find $f \circ g^{-1}$.
If $f(x)=\frac{4-5 x}{2}$, and $g(x)=x+6, x \in R$, find $f \circ g^{-1}$.(a) If $f(x)=\frac{4-5 x}{2}$, and $g(x)=x+6, x \in R$, find $f \circ g^{-1}$. (b) $P(x, y)$ divides the line joining $(7,-5)$ and $(-2,7) ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Find the limit \lim _{x \rightarrow \infty} \frac{x^{3}-6 x+1}{x^{2}+2 x-3} 1 answer 95 views Find the limit \lim _{x \rightarrow \infty} \frac{x^{3}-6 x+1}{x^{2}+2 x-3}Find the limit \lim _{x \rightarrow \infty} \dfrac{x^{3}-6 x+1}{x^{2}+2 x-3} ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 For the function f(x)=-3 x+4, find and simplify  \frac{f(x+h)-f(x)}{h}  1 answer 121 views For the function f(x)=-3 x+4, find and simplify  \frac{f(x+h)-f(x)}{h} For the function f(x)=-3 x+4, find and simplify  \frac{f(x+h)-f(x)}{h}  ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 Given that \(f(x)=2 x^{2}-3$ and $g(x)=x+1$ where $x \in R$. Find $g \circ f(x)$.
Given that $f(x)=2 x^{2}-3$ and $g(x)=x+1$ where $x \in R$. Find $g \circ f(x)$.Given that $f(x)=2 x^{2}-3$ and $g(x)=x+1$ where $x \in R$. Find $g \circ f(x)$. A. $2\left(x^{2}-1\right)$ B. $2 x^{2}+4 x-1$ C. \(2 x^{ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Simplify $\left(\dfrac{2 x^{3}}{8 y^{-4}}\right)^{-3}$
Simplify $\left(\dfrac{2 x^{3}}{8 y^{-4}}\right)^{-3}$Simplify $\left(\dfrac{2 x^{3}}{8 y^{-4}}\right)^{-3}$ ...
Evaluate $\lim _{x \rightarrow 1}\left(\frac{y-4 \sqrt{y}+3}{y^{2}-1}\right)$
Evaluate $\lim _{x \rightarrow 1}\left(\frac{y-4 \sqrt{y}+3}{y^{2}-1}\right)$Evaluate $\lim _{x \rightarrow 1}\left(\frac{y-4 \sqrt{y}+3}{y^{2}-1}\right)$ ...